Parental Diabetes Behaviors and Distress Are Related to Glycemic Control in Youth with Type 1 Diabetes: Longitudinal Data from the DINO Study. (10th December 2017) - Eilander, Minke M. A.; Snoek, Frank J.; Rotteveel, Joost; Aanstoot, Henk-Jan; Bakker-van Waarde, Willie M.; Houdijk, Euphemia C. A. M.; Nuboer, Roos; Winterdijk, Per; de Wit, Maartje
Abstract : Objective . To evaluate (1) the longitudinal relationship between parental well-being and glycemic control in youth with type 1 diabetes and (2) if youth's problem behavior, diabetes parenting behavior, and parental diabetes-distress influence this relationship. Research Design and Methods . Parents of youth 8–15 yrs (at baseline) (N = 174 ) participating in the DINO study completed questionnaires at three time waves (1 yr interval). Using generalized estimating equations, the relationship between parental well-being (WHO-5) and youth's HbA1c was examined. Second, relationships between WHO-5, Strength and Difficulties Questionnaire (SDQ), Diabetes Family Behavior Checklist (DFBC), Problem Areas In Diabetes-Parent Revised (PAID-Pr) scores, and HbA1c were analyzed. Results . Low well-being was reported by 32% of parents. No relationship was found between parents' WHO-5 scores and youth's HbA1c (β = − 0.052, p = 0.650 ). WHO-5 related to SDQ (β = − 0.219, p < 0.01 ), DFBC unsupportive scale (β = − 0.174, p < 0.01 ), and PAID-Pr (β = − 0.666, p < 0.01 ). Both DFBC scales (supportive β = − 0.259, p = 0.01 ; unsupportive β = 0.383, p = 0.017 ), PAID-Pr (β = 0.276, p < 0.01 ), and SDQ (β = 0.424, p < 0.01 ) related to HbA1c. Conclusions . Over time, reduced parental well-being relates to increased problem behavior in youth, unsupportive parenting, and parental distress, which negatively associate with HbA1c. More unsupportive diabetes parenting and distress relate to youth's problem behavior.